کاریگەری بەرزو نزمی لەسەر دابەشبوونی جوگرافی ڕووەکی خۆرسک لەناحیەی خورماڵ بە بەکارهێنانی بەرنامەی GIS و RS - درویش, ام کلثوم مصطفی; احمد, ڕێباز حمەغریب (Sulaimani Journal for Humanities, 2022)
The study area is located in the north of Halabja Governorate, Kurdistan Region, north of Iraq, the area of the area is about (267.8) km2, the study focused on clarifying and analyzing the effect of the altitude factor in terms of (slope, slope direction, height above sea level) on the geographical distribution of natural vegetation from where the density and diversity of natural plants in the region using both the GIS and RS program, and the study relied on the Regional Method، fundamentalist and analytical approach to achieve the objectives of the study, and the selection of the research topic is due to the fact that the study area characterized by a diverse topography as it is located within a complex mountainous region torsion in the Kurdistan region, which completely affected, on the natural vegetation, by projecting the data and figures obtained from the satellites onto a map using GIS and remote sensing, the study assumes that the altitude factor has an impact on the geographical distribution of the natural vegetation, diversity and density in the study area. To achieve the purpose of the study, the research topic was divided into two main topics: The first: presents the definition of the study area geographically in terms of location and topography. The second topic: analysis of the effect of the height factor on the natural plant (density, type) and the conclusion includes the conclusions and a list of references.